Understanding change with(in) law: The Niyamgiri case. (June 2016) - Chandra, Rajshree
This article seeks to understand the contrarian impulses embedded in the historic Supreme Court judgement in the 'battle for Niyamgiri' that resulted in tribal gram sabhas rejecting the bauxite mining proposal of the Odisha state government and transnational corporation, Vedanta. It proposes that the importance of the Niyamgiri case lies in the legal representation of indigeneity that emerges as a counterpoint to automatic assumptions of developmentalism and cultural homogeneity. However, rather than seeing this as an epistemic or discursive break in the practice of law, it proposes that we see the case 'jurisdictionally', as a practice of representation that is enacted through technologies and devices of law. It is important to understand that constitutive actors—lawyers, judges, ministers, experts, tribals—within specific jurisdictional spaces can change the prudence and diction in law, beyond the internal necessity of rules underwritten by tradition or dominant discourse. It is through this lens that the article sees the Niyamgiri story as inaugurating a particular form of lawful relations for indigeneity—one that becomes a part of case law history and precedent. No matter how tenuous, precedents such as Niyamgiri underwrite the prospect of future iterations of indigeneity.